Outcomes of Observance Privacy in Hospitalized Patients: A Qualitative Content Analysis - Tayebeh Hasan Tehrani (Hamadan University of Medical Sciences, 2020)
Introduction: In medical ethics, privacy is one of the main aspects of patient rights. Since the outcomes of respecting privacy as one of the dimensions of patient's rights are not clear, this study was performed to explore outcomes of observance for patient privacy in hospital. Methods: This study was conducted with qualitative research approach and contractual content analysis method. Participants included 20 patients hospitalized in the internal and surgical wards of Tehran's hospitals who were selected based on purposeful sampling. Data was collected using semi-structured interviews. Then data was analyzed based on conventional content analysis method and using the MAXQDA 10 software. Results: Analyzing the interviews with patients, 56 primary codes, 13 subcategories and 4 themes were extracted, which indicated the perception of participants for consequences of observance for privacy. These themes included: preservation and promotion of the dignity of the patient, compromise with the existing situation, health development and satisfaction. Conclusion: The results of this study showed outcomes of observance for patient’s privacy. With the treatment team's awareness of these consequences, the patients' expectations are respected, which leads to the provision of favorable health care and patient satisfaction.